Music therapy as a resource for the development of music perception in cochlear implant users: Case study - Reinert, Roberto Augusto Corrêa; Simões, Pierangela Nota; Cunha, Rosemyriam Ribeiro dos Santos (Seven Editora, 2024)
This study aimed to evaluate whether or not music therapy can help to develop music perception of cochlear implant (CI) users, thus improving their music appreciation. It is a longitudinal and prospective study that uses a mixed approach. In order to collect data, the Munich Music Questionnaire (MUMU) and the Music Perception Test BATUTA were applied, the latter being adapted to assess the perception of melody and timbre of an adult with congenital, bilateral, and profound hearing impairment (HI) who uses a unilateral CI. Eight music therapy sessions were carried out, using sound-musical activities with musical instruments to stimulate and develop music perception skills. At the end of the sessions, the musical perception test was reapplied with the result of 17 correct answers before and 20 correct answers after the music therapy sessions. The participant's responses to the MUMU indicated that music is of great importance in his life and brings him pleasure, along with emotional satisfaction. Furthermore, there was an increase in the number of correct answers and a decrease in repetitions of the BATUTA’s musical samples after each music therapy session. It was concluded that music therapy is a valuable resource for developing the music perception of individuals with hearing impairment who use CI. DOI:https://doi.org/10.56238/sevened2024.001-013